Penguatan Tata Kelola Keuangan untuk Pendanaan UMKM (Pendekatan Praktis dan Inovatif) di KP. Ciwindu Desa Ciwarna Kec. Mancak Kabupaten Serang - Febby Febriana; Riski Wisnu Prakoso; Harya Sunarya; Ainun Syahara; Dina Dina (Lembaga Pengembangan Kinerja Dosen, 2025)
The aim of Community Service Activities is to implement one of the Tri Darmas of Higher Education. Apart from that, it is hoped that with community service, the existence of universities can make a major contribution to the development and application of science to society. The methods used in this Community Service are expository, namely conveying material verbally and inquiry, namely learning that emphasizes critical and analytical thinking processes related to financial management skills, namely Strengthening Financial Governance for MSME Funding (Practical and Innovative Approach) in Kp. Ciwindu Village Ciwarna District. Mancak, Serang Regency. The results of community service obtained are increasing knowledge regarding the management of preparing financial reports and funding for MSMEs located at Kp. Ciwindu, Ciwarna Village, Kec. Mancak, Serang Regency, Banten Province. It is hoped that this training for the community will be able to prepare financial reports practically and increase financial literacy in the village environment.